Higher Education's Institutions Response to Statutory TQM Case Study - Munyanyiwa, Takaruza; Nyaruwata, Shepherd (IGI Global, 2021)
Quality is at the top of most agendas and improving quality is the most important task facing any higher education institution. High-quality education has become a key ingredient for socio-economic development. Many governments are putting more importance on the delivery of a quality education at institutions of higher learning. Enactment of pro higher education TQM legislation is now at the center of education delivery systems. In a highly competitive education sector, the success of academic institutions depends on the quality of education. This chapter presents a review of the responses of Higher Education Institutions in Zimbabwe to the introduction of statutory total quality management in education. Data and information for this study are collected through extensive literature and document review, interviewing experts, and personal experience. The feedback and insights and reviews are supported by TQM theory.